Low Temperature Grafting of MMA on to Coir Fibre - Lakshmi, N. S.; Babu, Sarika; Sebastian, Sumy; Ravi, P. K. (International Coconut Community, 2015)
Low temperature grafting of methyl methacrylate (MMA) on to coir fibre was carried out in aqueous medium using Potassium per sulphate (PPS) as an initiator under the catalytic influence of Ferrous ammonium sulphate (FAS). Optimization of various parameters of grafting viz. monomer, initiator and catalyst concentration, time and temperature was carried out to obtain the maximum tensile properties. Evidence of grafting was characterized from Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Thermal analysis (TGA). The maximum breaking stress (BS) of control and grafted coir fibre were 213.08 and 365.00 N/mm2 respectively. Hence the percentage of improvement of grafted coir fibre was found to be 71.30%. Increase in tensile properties with maximum BS observed under monomer (25%), initiator (0.75%) and catalyst (0.75%) concentration, time (150min) and temperature (500C) respectively. The t-test and Analysis of variance (ANOVA) were studied for statistical significance and the P values obtained were less than 0.05 which revealed that the value was highly significant for the improvement of mechanical strength on coir fibre by graft Co- polymerization.